Global, Regional, and National Burden of Breast Cancer, 1990–2021, and Projections to 2050: A Systematic Analysis of the Global Burden of Disease Study 2021 - Tong Deng; Hao Zi; Xing‐Pei Guo; Li‐Sha Luo; Ya‐Long Yang; Jin‐Xuan Hou; Rui Zhou; Qian‐Qian Yuan; Qing Liu; Qiao Huang; Gao‐Song Wu (Thoracic Cancer)
ABSTRACT Background This study analyzes the global burden of breast cancer (BC) over the past 30 years, identifies key risk factors, and projects future incidence and mortality through 2050. Methods Data were sourced from the 2021 Global Burden of Disease (GBD) database. The estimated annual percentage change (EAPC) was used to assess trends, and country development was measured using the Socio‐Demographic Index (SDI). Projections were conducted using Bayesian age‐period‐cohort and autoregressive integrated moving average models. Results In 2021, approximately 2.12 million new breast cancer cases and 674 199 deaths were recorded globally. From 1990 to 2021, incidence and prevalence increased, while mortality and disability‐adjusted life years (DALYs) declined overall. Regional and national variations were observed, alongside age and gender differences in the disease burden. A diet high in red meat and a high body mass index were the leading global risk factors for breast cancer deaths. The BC burden was positively correlated with SDI across 21 GBD regions. Decomposition analysis highlighted demographic factors as the main drivers of increased disease burden over the past three decades. Projections indicate that BC incidence will continue to rise through 2050. Conclusions While global BC mortality has decreased over the past 30 years, incidence continues to rise. Low‐SDI regions face increasing challenges, as incidence, mortality, and DALYs persistently climb. These findings underscore the need for targeted public health strategies and equitable resource distribution to mitigate the rising burden of breast cancer.